Socio-demographic and Clinical profile of Children with Typhoid Fever in a Tertiary Care Hospital - Rahat, Syeda Farzana; Chanda Shaha, Kartick; Sultana, Humayra; Rahman, MD Shafiqur; Rahman, Sheikh Hasibur (Medicine Today, 2025)
Introduction with Objective: The aim of this study was to assess the socio-demographic and clinical profile of children with typhoid fever in Dhaka. Materials and Methods: This observational study was carried out among 120 patients presenting with symptoms, signs and laboratory investigations diagnostic of typhoid fever in IPD and OPD of Paediatric department, Dhaka National Medical College Hospital, Dhaka, from April 2013 to October 2013. Widal test positive was included for the study. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: Majority of the patients (55%) belonged to 6-8 years. Male patients (n=72, 60%) were more than the female patients (n=48, 40%). Parents education of the study patients was observed that majority parents (n=42, 35%) were HSC level and 41 parents (34.16%) were primary level. Parents occupational status of the study patients was observed that majority (n=42, 35.0%) of the parents were skilled worker. Almost half (46.67%) of the patients drink boiled water. 40% patients used to take food from outside. Good sanitation was found in 61 patients (50.83%).115 patients (95.83%) had fever 5-10 days. Thirty four percents patients had anemia. 85% patients had coated tongue. 59 patients had abdominal tenderness. Palpable liver was found in 85% patients. Palpable spleen was found in 53.33% patients. 72 (60.0%) patients had To 1:160. 103 patients (85.84%) had TH 1:320. Conclusion: Safe water, sanitation and hygiene are critical for preventing the spread of typhoid. Medicine Today 2025, Vol.37 (1): 61-63